2018
DOI: 10.1101/353151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebral organoids at the air-liquid interface generate diverse nerve tracts with functional output

Abstract: Three-dimensional neural organoids are emerging tools with the potential for improving our understanding of human brain development and neurological disorders. Recent advances in this field have demonstrated their capacity to model neurogenesis 1,2 , neuronal migration and positioning 3,4 , and even response to sensory input 5 . However, it remains to be seen whether these tissues can model axon guidance dynamics and the formation of complex connectivity with functional neuronal output. Here, we have establish… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…One study used spring scissors to cut cortical organoids and reported the maintenance of structural integrity over repeated cutting and long-term culture, but the distribution of SATB2, CTIP2, and TBR1 did not exhibit upper-and deep-layer specificity at day 154 of culture (Watanabe et al, 2017). Another study used liquid-air interface culture for sectioned cerebral organoids (Giandomenico et al, 2019). Although the liquid-air interface culture significantly improved neuronal survivability, accelerated neuronal maturation, and promoted formation of aligned axonal tracks, it resulted in flattening of the tissue and the VZ and SVZ structures were not preserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study used spring scissors to cut cortical organoids and reported the maintenance of structural integrity over repeated cutting and long-term culture, but the distribution of SATB2, CTIP2, and TBR1 did not exhibit upper-and deep-layer specificity at day 154 of culture (Watanabe et al, 2017). Another study used liquid-air interface culture for sectioned cerebral organoids (Giandomenico et al, 2019). Although the liquid-air interface culture significantly improved neuronal survivability, accelerated neuronal maturation, and promoted formation of aligned axonal tracks, it resulted in flattening of the tissue and the VZ and SVZ structures were not preserved.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned protocols utilizing mechanical cutting and hyperoxia culture (Watanabe et al, 2017), or air-liquid interface culture (Giandomenico et al, 2019), were effective at reducing cellular hypoxia and improving cell viability, but the formation of distinct cortical layers was not achieved, suggesting that reducing interior cell death alone is insufficient. Through our systematic characterization of SNOs along their developmental trajectory, we propose that the formation of distinct cortical layers depends on a series of requirements fulfilled in the SNO method, but not in other protocols.…”
Section: Ll Resourcementioning
confidence: 99%
“…Organoids generated from induced pluripotent stem cells (iPSCs) have emerged as a scaled-down and three-dimensional model of the human brain, mimicking various developmental features at the cellular and molecular levels (Camp et al, 2015;Cederquist et al, 2019;Giandomenico et al, 2019;Lancaster and Knoblich, 2014;Lancaster et al, 2013;Luo et al, 2016;Mariani et al, 2012;Paş ca et al, 2015;Qian et al, 2016;Renner et al, 2017;van de Leemput et al, 2014;Xiang et al, 2017Xiang et al, , 2019. Despite recent advances in the understanding of their cellular diversity, there is no evidence that these organoids develop complex and functional neural network activity that resembles early human brain formation (Birey et al, 2017;Giandomenico et al, 2019;Quadrato et al, 2017). Therefore, have not yet clearly determined whether brain organoids are a suitable model for neural network dynamics (Kelava and Lancaster, 2016;Paş ca, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These functional aspects, as well as the excitatory/inhibitory postsynaptic currents, the neuromelanin-like granules structurally similar to those isolated from human substantia nigra tissues and the inactivating inward/outward currents, support the reliability of cerebral organoids for modeling human brain (Paşca et al, 2015; Jo et al, 2016; Li et al, 2017). Furthermore, recent whole-cell voltage clamp recordings of individual neurons from air-liquid interface cerebral organoids show improved long-term survival of the cells distributed in three-dimensional space (Giandomenico et al, 2018).…”
Section: Brain Organoid Functions Provided By Integrated Electrophysimentioning
confidence: 99%
“…To the best of our knowledge, only a few reports describing the functional connectivity of brain organoids coupled to planar MEAs have been published. For example, Monzel et al (2017) as well as Giandomenico et al (2018) recently derived human midbrain organoids and plated them over an integrated MEA system for recording (Table 2 and Figure 6D). In the future, cerebral organoids could be also coupled to three-dimensional MEAs (Musick et al, 2009; Yang et al, 2016) which better conform to their shape - for monitoring spontaneous or evoked neuronal signals from multiple layers.…”
Section: Brain Organoid Functions Provided By Integrated Electrophysimentioning
confidence: 99%